PENGEMBANGAN MEDIA PAPAN SUSUN BLOCK PUZZLE PADA MATERI OPERASI HITUNG GUNA MEMFASILITASI KEMAMPUAN COMPUTATIONAL THINKING SISWA SEKOLAH DASAR - Usamah, Yunita; Bagus Ardi Saputro; Ferina Agustini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Computational thinking is the ability of students to solve problems by breaking them down into several stages that are effective, efficient, and comprehensive. However, there are still many students in elementary school who still have difficulty in understanding computational thinking in solving problems, especially arithmetic. This research aims to develop computational thinking skills in mathematics lessons to support student learning in mathematics of computational operation materials. This research uses a research and development (R&D) approach with the ADDIE (Analysis, Development, Design, Implementation, Evaluation) design model. The development process is designed so that students can actively divide problems into simple ones, look for similarities between problems, see problems fundamentally, and develop solution steps in solving problems. In this study, a sample was used in grade 3 in one of the elementary schools in the city of Semarang which amounted to 22 students. Based on the results of the research, block puzzle stacking board media can be used by teachers as one of the learning media, especially in multiplication operation materials and can facilitate students' computational thinking skills.